2005
DOI: 10.1256/qj.04.33
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between concentric eye‐walls in super typhoon Winnie (1997)

Abstract: SUMMARYSuper typhoon Winnie had one of the largest eye-walls ever recorded in the western Pacific Ocean. The diameter of the outer eye-wall reached 370 km when Winnie passed through Okinawa on 16 August 1997. Observations revealed a 24-hour intensity cycle of concentric eye-walls after the large eye-wall formed. Using the Penn State University/National Center for Atmospheric Research mesoscale model MM5 with 3 km grid horizontal spacing on the finest nested mesh, Winnie was successfully simulated in terms of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Lander [] reported that Super Typhoon Winnie, which made landfall on the southeast coast of China in August 1997, had one of the two largest TC eye‐walls in the history of TC satellite and radar observations. The radius of Winnie's Force 6 (10.8 m s −1 ) surface wind circle was greater than 600 km, as revealed by a numerical simulation [ Zhang et al , ]. Winnie's huge size gave rise to a high number of TCHW events after landfall, which accounted for the high ratio of TCHW frequency to the number of ITCTs in 1997.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lander [] reported that Super Typhoon Winnie, which made landfall on the southeast coast of China in August 1997, had one of the two largest TC eye‐walls in the history of TC satellite and radar observations. The radius of Winnie's Force 6 (10.8 m s −1 ) surface wind circle was greater than 600 km, as revealed by a numerical simulation [ Zhang et al , ]. Winnie's huge size gave rise to a high number of TCHW events after landfall, which accounted for the high ratio of TCHW frequency to the number of ITCTs in 1997.…”
Section: Resultsmentioning
confidence: 99%
“…Super Typhoon Saomai (2006) made landfall in the provinces of Zhejiang and Fujian (Figure ), with powerful gusty winds that reached 75.8 m s −1 . Saomai affected 5.99 million population, killed at least 483 people, and caused 2.5 billion dollars of economic losses [ Liu et al , ; Zhang et al , ]. In addition, storm surges driven by TCHW is also one major hazard to coastal regions [ Lin et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the example shown in Figure 3 is typical of many concentric eyewall configurations, there are cases with much wider moats. For example, in the case of typhoon Winnie (1997) the moat was approximately 130 km wide (Lander, 1999;Zhang et al, 2005). In cases with such wide moats or with large vorticity in the moat, the Rossby length in the moat can be smaller than the moat width, in which case there will be large horizontal variation of subsidence across the moat.…”
Section: Prototype Concentric Eyewallsmentioning
confidence: 99%
“…Beyond the sensitivity of numerical TC simulations to convectivescale processes, part of the challenge in operational forecasting is that the exact physical factors responsible for SEF have not been discerned from a list of plausible mechanisms. In recent years, improved resolution in fullphysics TC simulations has resulted in numerous studies of SEF and ERCs (e.g., Zhang et al 2005;Terwey and Montgomery 2008;Wang 2008aWang ,b, 2009Hill and Lackmann 2009;Hogsett and Zhang 2009;Wu et al 2009;Judt and Chen 2010;Martinez et al 2011;Zhou and Wang 2011;Abarca and Corbosiero 2011;Chen et al 2011;Wu et al 2012;Huang et al 2012, hereafter HMW12;Fang and Zhang 2012, hereafter FZ12). This suggests that the understanding and predictability of SEF will continue to improve.…”
Section: Introductionmentioning
confidence: 99%